Gen dan QTL Pengendali Umur pada Kedelai - Tasma, I Made (Jurnal AgroBiogen, 2013)
Traits that control time of flowering andmaturity in soybean determine harvesting time of a soybeancultivar. In Indonesia, early maturing soybean cultivars areimportant at short period growing seasons due to the watershortage in dry planting season. Shorter period of growingseason would increase the crop harvest index. Geneticdiversity of the present soybean germplasm collection islow. Diversity improvement through introduction fromcountries with four seasons faced difficulty due todifferences in growth adaptability. Technology for developinggermplasm with a broader adaptation will facilitategermplasm movement from a more diverse environmentalgrowth. The objective of this review was to describe howthe time of flowering and maturity are controlled in soybean.The review is supported by flowering time mechanism ofthe model plant Arabidopsis thaliana as the genetics offlowering time has been intensively studied in this modelplant. Transition from vegetative to reproductive developmentis the outcome of the activation of genes responsiblefor floral organ formation. Initial activation is generally theresult of environmental cues indicating the appropriate timeto flower. Studies from Arabidopsis showed that transitionfrom vegetative to reproductive stage is complex involvingmany genes and several genetic pathways. In soybean, timeof flowering and maturity are controlled by at least ninegenes, E1 to E8 and Dt1. The genes interact with daylengthand temperature. Major and minor QTLs controlling thetraits were identified using various mapping populations.The major QTLs were detected at various populations withdiverse genetic backgrounds tested at diverse environmenttalconditions. Some of the QTLs were associated with the Egenes and some others were not. Several Arabidopsisflowering gene homologous sequences were also mappedon the soybean genome. The E gene markers and the QTLswith large effect for reproductive traits are breeder targetsfor breeding and development of soybean photoperiodinsensitive germplasm. Genes for flowering time isolatedfrom Arabidopsis can be used to develop transgenicsoybean with broader adaptation. Technology for developmentof soybean germplasm with broader adaptation willfacilitate the soybean germplasm movement from diverseenvironmental growth conditions to support systematic andsustainable national soybean breeding programs.